Analysis of the dynamics of the decay D + → K S 0 π 0 e + ν e $$ D^{+}→ K_S^0π^0{e}^{+}{ν}_e $$ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract The branching fraction of D + → K S 0 π 0 e + ν e $$ D^{+}→ K_S^0π^0{e}^{+}{ν}_e $$ is measured for the first time using 7.93 fb −1 of e + e − annihilation data collected at the center-of-mass energy s $$ \sqrt{s} $$ = 3.773 GeV with the BESIII detector operating at the BEPCII collider, and is determined to be B D + → K S 0 π 0 e + ν e = 0.881 ± 0.017 stat . ± 0.016 syst . % $$ \mathcal{B}\left(D^{+}→ K_S^0π^0{e}^{+}{ν}_e\right)=\left(0.881± {0.017}_{stat.}± {0.016}_{syst.}\right)% $$ . Based on an analysis of the D + → K S 0 π 0 e + ν e $$ D^{+}→ K_S^0π^0{e}^{+}{ν}_e $$ decay dynamics, we observe the S-wave and P-wave components with fractions of f S-wave = (6.13 ± 0.27stat. ± 0.30syst. )% and f K ¯ ∗ 892 0 = 93.88 ± 0.27 stat . ± 0.29 syst . % $$ {f}_{{\overline{K}}^{* }{(892)}^0}=\left(93.88± {0.27}_{stat.}± {0.29}_{syst.}\right)% $$ , respectively. From these results, we obtain the branching fractions B D + → K S 0 π 0 S − wave e + ν e = 5.41 ± 0.35 stat . ± 0.37 syst . × 10 − 4 $$ \mathcal{B}\left(D^{+}→ {\left(K_S^0π^0\right)}_{S-wave}{e}^{+}{ν}_e\right)=\left(5.41± {0.35}_{stat.}± {0.37}_{syst.}\right)× {10}^{-4} $$ and B D + → K ¯ ∗ 892 0 e + ν e = 4.97 ± 0.11 stat . ± 0.12 syst . % $$ \mathcal{B}\left(D^{+}→ {\overline{K}}^{* }{(892)}^0{e}^{+}{ν}_e\right)=\left(4.97± {0.11}_{stat.}± {0.12}_{syst.}\right)% $$ . In addition, the hadronic form-factor ratios of D + → K ¯ ∗ 892 0 e + ν e $$ D^{+}→ {\overline{K}}^{* }{(892)}^0{e}^{+}{ν}_e $$ at q 2 = 0, assuming a single-pole dominance parameterization, are determined to be r V = V 0 A 1 0 = 1.43 ± 0.07 stat . ± 0.03 syst . $$ {r}_V=\frac{V(0)}{A_1(0)}=1.43± {0.07}_{stat.}± {0.03}_{syst.} $$ and r 2 = A 2 0 A 1 0 = 0.72 ± 0.06 stat . ± 0.02 syst . $$ {r}_2=\frac{A_2(0)}{A_1(0)}=0.72± {0.06}_{stat.}± {0.02}_{syst.} $$ .